The Influence of Sharia Banks’ Corporate Image and Sharia Service Standardization on the Intention to Recommend to Others: The Mediating Role of Customer Satisfaction - Warsito, Chandra; Solikhin, Iin; Farhah, Nida Umi; Wibisono, Dhika Dzulkarnain (International Journal of Management and Sustainability, 2022)
Grounded in marketing theory, the current study aims to investigate the role of corporate image and service standardization on the intention to recommend to others, as well as the role of customer satisfaction as a mediator. Following a quantitative research design, the cross-sectional field survey was conducted on a sample of 200 customers of Islamic banks in Indonesia. The data were analyzed through SmartPLS and SPSS to test the proposed hypotheses, and the results revealed a positive significant impact of Sharia banking image and Sharia service standardization on people’s intention to recommend the service to others. Similarly, customer satisfaction also revealed a positive impact on the intention to make recommendations. Additionally, the mediation of customer satisfaction rendered significant support from study results as proposed in the theoretical model. The study is incremental in Islamic banking literature for integrating and testing a unique theoretical framework in an Indonesian context. Several theoretical and policy implications as well as future research directions are suggested.